Some aspects of mechanical characteristics forming in carbon materials based on exfoliated graphite - Sementsov, Yu. I.; Pyatkovsky, M. L.; Prikhod'ko, G. P.; Ogenko, V. M.; Sidorenko, I. G.; Yanchenko, V. V. (Chuiko Institute of Surface Chemistry National Academy of Sciences of Ukraine, 2002)
Structural and phase transformations in precursors of the exfoliated graphite (EG) and an effect of various conditions of heating, extension and chemical modification on structure and physical properties of EG-based carbon materials were studied. Some aspects of the forming of the strength characteristics of low-density materials from EG at the principle stages of their preparation are considered. The preliminary results of obtaining of aggregate models of EG-carbon and EG‑carbon-carbon fibre are considered.